An Analysis of Code-Mixing Used by the Lecturer at Universitas Cokroaminoto Palopo - Rahmawati Upa; Reski Yusrini Islamiah Yunus; Dedan Marthen; Sri Rahayu (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research aims to find out the types of code-mixing and student’s perception on code-mixing used by the lecturer in English class. This research used both Qualitative and Quantitative methods. The subject in this research are the lecturer and the first year of science students at Cokroaminoto Palopo University. The instrument of this research are observation sheet, recorder, and questionnaire. The result of this research shows that (1) There are three types of code-mixing found in the lecturer’s utterances during the English teaching-learning process. They are Intra sentential, intra lexical, and involve a change of pronunciation and the results showed that the most frequent is intra sentential. (2) Regarding students’ perception of code-mixing, the researcher found that most students agreed to the use of code-mixing in the English teaching-learning process in the first year of science student at Cokroaminoto Palopo University because code-mixing can make their communication with their lecturer more effective.